THE SIGNIFICANCE OF TRADITIONAL CRAFTSMANSHIPS IN THE ECONOMIC DEVELOPMENT OF LOCAL INDUSTRY ENTERPRISES OF SURKHONDARYO REGION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, after World War II, the establishment of local industrial enterprises in the southern regions of Uzbekistan, the province of Surxondary, and its republic, in the 1950's and 1980's, artifacts were also launched in Shorchi, Denov, Jarkogon, Boysun, Qarshi, Tajikistan, and other districts, including craftsmanship, pioneering, craftsmanship, Opinions on the introduction of new technologies for the production of atlas,unscrupulous fabrics are broadened based on archive materials.